Peran Tabayyun dalam Islam untuk Mengatasi Hoax dan Misinformasi di Media Sosial - Muhafazhoh Hasanah Al-Faqiha; Fatimah Azzahra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of social media has made it easier to disseminate information, but it has also given rise to various problems such as hoaxes and misinformation that can lead to social conflict, division, and misunderstanding in society. In Islam, the concept of tabayyun is an important principle in receiving and conveying information. This study aims to analyze the role of tabayyun in addressing hoaxes and misinformation on social media from an Islamic perspective. The method used is qualitative research with a literature study approach through the study of the Qur'an, hadith, and various scientific sources related to social media and digital literacy. The results show that tabayyun plays an important role as a form of verifying information before believing and disseminating it to others. The application of tabayyun can increase critical thinking, moral responsibility, and social media ethics among the community. Thus, the values ​​of tabayyun are relevant to be applied in the digital era to create a social media environment that is healthier, safer, and free from the spread of false information.